Morphologic lesions of membranous nephropathy in association with various demographic and laboratory parameters of patients; a single center study - Sara Zamani; Hamid Nasri (Society of Diabetic Nephropathy Prevention, 2020)
Introduction: Nephrotic syndrome is an important clinical presentation of glomerular diseases that is classified into several types based on the findings of renal biopsy. Membranous neuropathy is the most common cause of nephrotic syndrome, especially in adults over 40 years of age, which may lead to end-stage renal failure. Objectives: The present study aimed to assess the association of morphologic lesions of membranous nephropathy (MN) on renal biopsy with various demographic and laboratory parameters of the patients. Patients and Methods: This study was performed on renal biopsies, which were referred to the laboratory with the diagnosis of MN. To reach a definite diagnosis of MN, an immunofluorescence study (IgG, IgA, IgM, C1q and C3 antibody deposits) was conducted for all patients. Light microscopy was conducted to categorize the morphologic lesions of the glomeruli and interstitial area. The percentage of interstitial fibrosis/tubular atrophy was assessed too. Additionally, age, gender, and 24- hour urinary protein and serum creatinine were recorded. Results: Among 175 idiopathic MN patients, 98 were male (56%). The patients' age was between 14 and 84 years (mean; 42±15 years). The mean of serum creatinine and 24-hour urine protein were 1.05 ± 0.31 mg/dL and 2779.56± 1495.80 mg/d, respectively. We found a significant correlation between gender and serum creatinine level, which was higher in men (P<0.001). Moreover, there was a significant, positive correlation between serum creatinine and age of patients (P<0.001, r=0.25). Additionally, there was a significant correlation between serum creatinine and interstitial fibrosis (P=0.001). We found a significant correlation between serum creatinine and the pathologic stage of glomeruli (P=0.003). The stages of glomeruli were also associated with the proportion of interstitial fibrosis (P=0.001) and C3 deposition rate (P=0.002). IgG deposition score was also significantly different in age ranges over and under 40 years of age (P=0.001). The 24-hours proteinuria had no correlation with other laboratory parameters and microscopic findings. Conclusion: In accordance with other studies, we found that MN is more common among male patients. The positive correlation between serum creatinine and proportion of interstitial fibrosis is in concordance with previous studies. We found a positive correlation between serum creatinine and glomerular morphologic stages. It may show the importance of glomerular damage intensity in prognosis and survival of patients.